(2x+5)(6-3x)=0

Simple and best practice solution for (2x+5)(6-3x)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+5)(6-3x)=0 equation:


Simplifying
(2x + 5)(6 + -3x) = 0

Reorder the terms:
(5 + 2x)(6 + -3x) = 0

Multiply (5 + 2x) * (6 + -3x)
(5(6 + -3x) + 2x * (6 + -3x)) = 0
((6 * 5 + -3x * 5) + 2x * (6 + -3x)) = 0
((30 + -15x) + 2x * (6 + -3x)) = 0
(30 + -15x + (6 * 2x + -3x * 2x)) = 0
(30 + -15x + (12x + -6x2)) = 0

Combine like terms: -15x + 12x = -3x
(30 + -3x + -6x2) = 0

Solving
30 + -3x + -6x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '3'.
3(10 + -1x + -2x2) = 0

Factor a trinomial.
3((2 + -1x)(5 + 2x)) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(2 + -1x)' equal to zero and attempt to solve: Simplifying 2 + -1x = 0 Solving 2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = 0 + -2 -1x = 0 + -2 Combine like terms: 0 + -2 = -2 -1x = -2 Divide each side by '-1'. x = 2 Simplifying x = 2

Subproblem 2

Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5

Solution

x = {2, -2.5}

See similar equations:

| 7x+4y+2z=1650 | | 6(x-2)=35 | | x^5-3*x^3=0 | | x^2+y^2+10x-14y+6=0 | | x*y=351 | | 6x+4y+3z=63 | | 3x+62=9x-10 | | px-qx=n | | Sec(x-pi/4) | | 0=-240 | | -4(2y+3)=-18 | | 16w^2-24w+9=0 | | X-9x+2x= | | 2q^2+5q-250=0 | | 5a+3=1 | | 2(3g+2)=1-2(12g+8) | | -63=-5(a+5)-4(1+3a) | | (6.673e-11)(8.24e28)(5.75e22)/(3.43e4)2 | | 7m-4=17 | | 250=15x+18y | | 12+5v=2v-2 | | -2(8p+5)-2(7p+8)=4 | | r(5r+4)=0 | | 76/19 | | (x-27)/x=0.65 | | -9y+63=0 | | -2y-58=0 | | -6(6n-4)-6(1+8n)=18 | | |p-2s|/2=w | | 2x-58=0 | | (7x^2+5)-(2x^2-5)= | | 5+40=0 |

Equations solver categories